Decreased KCNE2 Expression Participates in the Development of Cardiac Hypertrophy by Regulation of Calcineurin–NFAT (Nuclear Factor of Activated T Cells) and Mitogen-Activated Protein Kinase Pathways. (June 2017) - Liu, Wenjuan; Deng, Jianxin; Ding, Wenwen; Wang, Gang; Shen, Yuanyuan; Zheng, Junmeng; Zhang, Xiaoming; Luo, Yizhi; Lv, Chifei; Wang, Yonghui; Chen, Liqing; Yan, Dewen; et al.
Abstract : Background—: KCNE2 is a promiscuous auxiliary subunit of voltage-gated cation channels. A recent work demonstrated that KCNE2 regulates L-type Ca 2+ channels. Given the important roles of altered Ca 2+ signaling in structural and functional remodeling in diseased hearts, this study investigated whether KCNE2 participates in the development of pathological hypertrophy. Methods and Results—: We found that cardiac KCNE2 expression was significantly decreased in phenylephrine-induced cardiomyocyte hypertrophy in neonatal rat ventricular myocytes and in transverse aortic constriction–induced cardiac hypertrophy in mice, as well as in dilated cardiomyopathy in human. Knockdown of KCNE2 in neonatal rat ventricular myocytes reproduced hypertrophy by increasing the expression of ANP (atrial natriuretic peptide) and β-MHC (β-myosin heavy chain), and cell surface area, whereas overexpression of KCNE2 attenuated phenylephrine-induced cardiomyocyte hypertrophy. Knockdown of KCNE2 increased intracellular Ca 2+ transient, calcineurin activity, and nuclear NFAT (nuclear factor of activated T cells) protein levels, and pretreatment with inhibitor of L-type Ca 2+ channel (nifedipine) or calcineurin (FK506) attenuated the activation of calcineurin–NFAT pathway and cardiomyocyte hypertrophy. Meanwhile, the phosphorylation levels of p38, extracellular signal-regulated kinase 1/2, and c-Jun N-terminal kinase were increased, and inhibiting the 3 cascades of mitogen-activated protein kinase reduced cardiomyocyte hypertrophy induced by KCNE2 knockdown. Overexpression of KCNE2 in heart by ultrasound-microbubble–mediated gene transfer suppressed the development of hypertrophy and activation of calcineurin–NFAT and mitogen-activated protein kinase pathways in transverse aortic constriction mice. Conclusions—: This study demonstrates that cardiac KCNE2 expression is decreased and contributes to the development of hypertrophy via activation of calcineurin–NFAT and mitogen-activated protein kinase pathways. Targeting KCNE2 is a potential therapeutic strategy for the treatment of hypertrophy. Abstract : Supplemental Digital Content is available in the text.